Meconopsis (sect. Impeditae) Grey-Wilson, Gen. - Elvebakk, Arve; Bjerke, Jarle W. (Zenodo, 2024)
4.3. Meconopsis sect. Impeditae Grey-Wilson, Gen. Meconopsis: 46. 2014 Type species. Meconopsis impedita Prain. Notes. Section Impeditae Grey-Wilson (Grey-Wilson 2014) partly overlaps with section Forrestianae as monographed later by Yoshida and Sun (2019 a) and referred to above. Two new species of Impeditae , M. angustipetala W. T. Wang and M. brachynema W. T. Wang, were described from China (Wang 2019). Published as part of Elvebakk, Arve & Bjerke, Jarle W., 2024, Papaver recircumscribed: A review of neighbouring Papaveraceae genera, including Afropapaver nom. et stat. nov. and Oreomecon, a large, Arctic-Alpine genus, pp. 105-188 in PhytoKeys 248 on pages 105-188, DOI:10.3897/phytokeys.248.121011